Review of the potential of bioactive compounds in seaweed to reduce histamine formation in fish and fish products - Muhammad Maskur; Asep Awaludin Prihanto; Muhamad Firdaus; Rovina Kobun; Rahmi Nurdiani (Italian Journal of Food Safety)
The formation of histamine in food is influenced by temperature, and histamine growth can be inhibited by maintaining a cold chain. However, simply relying on temperature control is insufficient, as certain bacteria can produce the enzyme histidine decarboxylase even at temperatures below 5°C. To address this issue, various methods, such as modified atmosphere packaging, high hydrostatic pressure, and irradiation, have been developed to control histamine in fishery products. However, these methods often require significant investments. Therefore, there is a need for a cost-effective solution to overcome this problem. This review explores a cost-effective solution through the utilization of bioactive compounds derived from underexplored seaweeds. Seaweed bioactive compounds, either in their pure form or as extracts, offer a promising alternative method to regulate histamine generation in fishery products due to their antibacterial activity, and this review provides comprehensive insights into the potential of different seaweed-derived bioactive compounds as inhibitors of histamine production, detailing their diverse applications in fishery products. It also explores the mechanism by which bioactive compounds prevent histamine formation by bacteria, focusing on the potential of seaweed bioactive compounds to inhibit bacterial histidine decarboxylase. Future trends in the inhibition of histidine decarboxylation are also discussed. The bioactive compounds considered, such as flavonoids, alkaloids, terpenes, and phenolic acids, exhibit their antibacterial effects through various mechanisms, including the inhibition of DNA and RNA synthesis, disruption of cytoplasmic and cell membranes, and inhibition of enzymes by reacting with sulfhydryl groups on proteins. In conclusion, the integration of underexplored seaweeds in fishery product preservation represents a promising and innovative approach for future food safety and sustainability.